Influence Produced by the Operation of the Power Units of Thermal Power Plants in the Maneuver Load Mode on the Reliability and Accident Rate of Power Equipment - Chernousenko, Olga Yuryevna; Peshko, Vitaliy Anatoliyovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
Due to the insufficient amount of maneuver powers for consolidated power systems in Ukraine pulverized-coal units that were designed for the operation in the base section of the schedule of electric loads are used for the power control. The current state of energy generating equipment available in Ukraine has been analyzed, the drawbacks of the operation of power units with regard to the normative base approved by the Ministry of Power Engineering and Fuel Industry of Ukraine have been revealed. Influence of the operation of the power units of thermal power plants in Ukraine in the maneuver mode on the reliability and accident rate of power equipment has been analyzed and the accident rate indicators and the specific indicators of equipment reliability have been calculated. It has been established that according to the current state of the equipment the operation in the maneuver mode is undesirable and requires the development of a special normative base because it causes a considerable wear of key assets. A number of emergency stops and emergency repair hours for the thermal power plants of the ²ENERGO² Thermal Power Plant is indicative of an increased accident rate during the operation period of 2012 to 2015. Proceeding from the character of an increased number of emergency stops and emergency repair hours for thermal power plants we can make a conclusion that these indicators will considerably increase in 2016, if operated in the maneuver mode of daily start-stop.